Unusual case of postpartum gingival enlargement: diagnosis and management - Arora, Shipra; Ahad, Abdul; Tandon, Shruti; Lamba, Arundeep; Faraz, Farrukh (International Journal of Medicine, 2016)
Gingival enlargement is a clinical condition that has been widely studied. Usually, it is related to specific local or systemic factors. However, it is difficult sometimes to find out a definite etiology, and treatment has to be done according to presenting clinical features.Â  This article presents an unusual case of gingival enlargement that occurred after pregnancy without any clear underlying etiology. A female aged 31 years reported with gingival enlargement and mobility of teeth during lactation period. Gingival enlargement had started 2 months after child birth.Â  All female sex hormones were found to be within normal limits. Karyotyping was also found to be normal, without any genetic alteration. Radiographic analysis revealed generalized severe crestal bone loss. After phase I periodontal therapy, enlargement was managed surgically under local anaesthesia. On histological examination of excised specimen, tissue was found to be hyperplastic. Although a definite etiology could not be ascertained, the treatment was successful and there has been no recurrence after one year post-treatment interval.